Pathway Analysis of the Influence of Islamic Quality of Service, Location, Price, and Quality of Products Labeled Halal on Customer Loyalty through Customer Satisfaction of Wardah Cosmetics on Customers in North Sumatra - Tio Astir Aulia Matondang; Chuzaimah Batubara; Nur Ahmad Bi Rahmadi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The halal industry continues to show positive development and growth every year. Indonesian people’s consumption of halal products continues to increase, even among the largest in the world. Marketing a product or modifying a product for a company is intended to satisfy consumers or customers. Customer satisfaction is always a top priority for every company. The purpose of this study was to determine the direct and indirect effect of Islamic service quality, location, price, and product quality on the totality of Wardah cosmetic customers in North Sumatra through customer satisfaction. This research method uses a quantitative approach with pathways and uses the help of the SPSS version 20.0 program. This study used a questionnaire with a sample of 100 respondents. The results showed that partial service quality had an effect on customer loyalty, location had a partial effect, religiosity had a partial effect and self-concept had no partial effect on customer loyalty. Prices affect customer loyalty and product quality affects customer loyalty. Customer satisfaction affects customer loyalty. Islamic service quality influences customer satisfaction. The location has no effect on customer satisfaction, price partially has an effect, and product quality has a significant effect on customer satisfaction. From the results of the significance test, it was obtained that Islamic service quality, location, and product quality had no significant and significant effect on customer loyalty through customer satisfaction for wardah cosmetics in North Sumatra. As for the price variable, it has a significant and significant effect on customer loyalty through customer satisfaction for Wardah cosmetics in North Sumatra. with a confidence level of 95% or an error rate of 5%.